Reduction of Amphotericin B-Induced Renal Tubular Apoptosis by N-Acetylcysteine - (:unkn) unknown (AMER SOC MICROBIOLOGY, 2009)
The reduction of amphotericin B (AmB)-induced renal tubular apoptosis and nephrotoxicity by N-acetylcysteine (NAC) in a murine model was evaluated. Four groups of rats were treated with AmB for 5 days, and each group concomitantly received two doses of 30, 60, or 120 mg of NAC/kg of body weight/day or sterile water for 5 days. Groups that received concomitant NAC at any dose had significantly decreased levels of apoptosis compared to that in animals receiving AmB only (48.8% versus 27.4, 23.6, or 23.5%, respectively; P < 0.001).
Keywords: LIPID FORMULATIONS; NEPHROTOXICITY; DEOXYCHOLATE; TOXICITY; NEPHROPATHY; PREVENTION; 5-PERCENT; TOLERANCE; EMULSION; DEXTROSE